DETERMINASI SOSIAL LINGKUNGAN KERJA DAN EPIDEMIOLOGI MANAJERIAL: TINJAUAN LITERATUR DAMPAK KOMUNIKASI INTERNAL DAN PARTISIPASI TERHADAP KEPUASAN KERJA PERAWAT MELALUI MEDIASI MOTIVASI KERJA DI RSUD PROVINSI NTB - Sadikin Apriadi; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2026)
Background: Nurse job satisfaction is a crucial indicator of healthcare service effectiveness at RSUD Provinsi NTB. However, managerial dysfunction often acts as a systemic barrier that diminishes medical staff performance. Objective: This study aims to analyze the social determinants of the work environment through the impact of internal communication and participation on nurse job satisfaction, with work motivation as a mediating variable within a managerial epidemiology framework. Method: This study employs a Systematic Literature Review (SLR) method. Literature searches were conducted via Scopus and Google Scholar databases spanning 2016-2026. Selected articles were analyzed using qualitative synthesis techniques to identify relationship patterns between variables. Results: Findings indicate that transparent internal communication and active participation in decision-making significantly enhance job satisfaction. Work motivation is proven to be a key mediator that strengthens the positive influence of the social environment on nurses' psychological well-being. From a managerial epidemiology perspective, communication failure is identified as a “risk determinant” that can trigger a collective decline in service quality. Conclusion: The integration of effective communication and broad participatory spaces is essential for RSUD Provinsi NTB management to create a healthy and motivating work environment